Prevalence of overweight and its associated factors among selected higher secondary schools adolescents of Kathmandu Metropolitan City, Nepal - Karishma Bhandari; Sheetal Bhandari; Manish Rajbanshi; Richa Aryal; Sagun Magar; Lokendra Oli; Mohandev Joshi; Bishnu Prasad Choulagai (PLoS ONE, 2025)
Overweight is highly prevalent in lower- and middle-income countries (LMICs), including Nepal. Due to the rapid physical and mental growth among adolescents, they are nutritionally vulnerable and sensitive to environmental factors and dietary habits. This study aimed to determine the prevalence of overweight and its associated factors among adolescents of higher secondary schools in Kathmandu Metropolitan City (KMC) of Nepal. A cross-sectional study was conducted among 282 adolescents in higher secondary schools. A stratified random sampling technique was used to select the participants for data collection. The frequencies, percentages, mean, and standard deviation were used to describe the characteristics of the participants. Binary logistic regression was performed to determine the association between individual characteristics and the prevalence of overweight. All the tests were performed at a 95% Confidence Interval (CI), and variables with p-values below 0.05 were considered statistically significant. The mean (±SD) age of the participants was 16.8 ± 0.1 years. The majority of the participants (66.3%) were from private schools. Around 13.4% of the participants were overweight. Characteristics such as type of school (AOR: 2.6, CI: 1.9–8.2), father’s education (AOR: 2.1, CI: 1.7–6.5), access to physical activity at school (AOR: 1.2, CI: 1.1–4.6), and pocket money for lunch at school (AOR: 0.3, CI: 0.2–0.5) were found to be significantly associated with overweight among adolescents in this study. This study found that a notable proportion of adolescents were overweight and were influenced by socio-economic and demographical characteristics such as education, income level, school type, and level of physical activity. School-based interventions and programs should be carried out to promote healthy eating and physical activity among adolescents. A holistic approach, including parental education on nutrition, controlling pocket money to reduce unhealthy purchases, and adding physical activities to school programs, should be tailored to the school setting to reduce the risk of being overweight.